Valoración de la eficiencia productiva de maíz (Zea mays l.), en sistemas de rotación de cultivo con trigo y fréjol arbustivo, en la localidad de Laguacoto III, provincia Bolívar - Vásquez Moreta, Franklin Reinaldo (2022)
Corn is among the four global food crops on the planet, along with wheat, rice and potato. It is the main source of energy within the value chain for both human and animal food through direct consumption and various by-products within the agroindustry. The Bolívar province is the largest producer of soft corn with 36%. However, due to several adverse factors such as climate change (CC), deterioration of natural resources, genetic erosion, and intensive monocultures in conventional tillage, the sustainability of local SP is at risk. Crop rotation is very important as it helps to return nutrients to the soil, it also works to interrupt pest and disease cycles, it increases the biomass content in the root structures of different crops. This research process was carried out in the locality of Laguacoto III, located at an altitude of 2632 m, with a clay loam soil type. The objectives were: i) Compile data from secondary sources with the main agronomic components in the corn crop, ii) Evaluate the productivity of crops in rotation, focused on conservation agriculture, iii) Generate a database of the productive components of corn, wheat and bush beans, in the fifth year of validation of the conservation agriculture system. A Randomized Complete Block Design (RCBD) with 5 treatments and 3 replications was used, and analysis of variance, economic analysis, Tukey's test at 5%, correlation, linear regression and B/C ratio analysis were carried out. The main results were different where it was recorded that in the percentage of emergence of corn treatments was the T1 with 73.92%, and the lowest was the T3 with 44.78%, in the days to male flowering the three treatments in studies provided an average of 127 days, and 132 days to female flowering, being the T3 treatment with the highest plant height with 325.70cm and the same treatment presented the lowest stalk diameter of 1.84cm and the highest height of ear insertion with 165.87cm. The best ear diameter was reflected in T1 with 5.94 cm, at the same time this treatment presented the smallest ear length with 15.24 cm, while T3 presented the best ear length with 17.84 cm, the three treatments presented between 11 and 12 rows per ear, the highest shelling percentage was reflected in T3 with 81.06% and the lowest average in T2 with 55.06%. In the weight of 100 dry grains of the corn treatments, the best was presented in T1 with 653.33 g at the same time was the best in yield with 3656.90 kg/ha, while the lowest average of 100 dry grains and yield was in T3 with 579 g and 2957.50 kg/ha, the best biomass yield was in T3 with 14123 kg/ha, and the lowest yield in T1 with 12491 kg/ha, the best yield obtained in the wheat crop was in T2 with 3678 kg/ha, and the lowest in T1 with 2345, in the biomass yield was the best in T1 and T2 with 12678 kg/ha, and the lowest in T8 with 11234 kg/ha, and finally the best bean yield was in the variety huevo de quinde with 2365 kg/ha, and the lowest average was obtained in the variety INIAP-427 with 1880 kg/ha.